Long-term outcome of a cohort of adults with autism and intellectual disability: A pilot prospective study. (January 2017) - Fusar-Poli, Laura; Brondino, Natascia; Orsi, Paolo; Provenzani, Umberto; De Micheli, Andrea; Ucelli di Nemi, Stefania; Barale, Francesco; Politi, Pierluigi
Highlights: Long-term outcome of patients with autism and intellectual disability has been rarely investigated in literature. We evaluated variation in adaptive abilities in a cohort of 22 adult patients. Adaptive abilities remained stable over ten years according to VABS raw scores. VABS standard scores showed an improvement in adaptive abilities. Abstract: Background: Autism spectrum disorders (ASD) are a long-life condition frequently associated with intellectual disability. To date, long-term outcome has been investigated mostly in ASD people with average or above-average intelligence and there is a paucity of data about autistic adults with comorbid intellectual disability. Aims: The aim of the present study is to assess long-term variations of adaptive abilities in a sample of autistic adults with intellectual disability and severe language impairment. Methods and procedures: 22 adults (17 males and 5 females) affected by autism and intellectual disability were recruited and evaluated after their admission in an Italian farm-community. Vineland Adaptive Behavior Scales (VABS) were used as outcome measure for adaptive abilities. After ten years the measurement was repeated in order to study the evolution of patients' skills along time. Additionally, sociodemographic variables, changes in medication and comorbidities were recorded. Outcomes and results: No statistically significant improvement neither deterioration was found according to VABS raw scores in the entire sample. On the contrary, a significant improvement was evident in standard scores for the Adaptive Behavior Composite Scale and for each domain. Conclusions and implications: In general, our patients remained stable in adaptive abilities. However, our results are not generalisable to the entire autistic population, but only to inpatients with autism and comorbid intellectual disability. New measures should be developed in order to better assess changes in this particular population.